PENGARUH PENGGUNAAN ASSESSMENT WORDWALL TERHADAP HASIL BELAJAR SISWA SMA - Ernasari, Ernasari; Meilina, Ike Lusi (Universitas Jember, 2024)
Learning motivation is an important thing that students must have in learning. Learning motivation is an encouragement for students to be able to carry out learning well to achieve a learning goal. However, not all learning processes can create good learning motivation for students, this also affects student learning outcomes, even though learning success can be seen one way from learning outcomes. student. This research aims, first, to determine the differences in learning motivation between students who use Wordwall assessment media and those who use test paper assessments. Second, to determine the difference in learning motivation between students who use Wordwall assessment media and those who use test paper assessment media. This research uses an experimental method with a Posttest-Only Control Group Design. The findings show that the average learning outcomes of students who use Wordwall assessment media are higher than students who use paper tests. Apart from that, the average learning motivation score of students who use Wordwall assessment media is higher than students who use paper tests. It can be sai, that this research has obtained results that show the influence of using wordwall assessment media on learning motivation and better learning outcomes because of its attractive features.